2011
DOI: 10.1158/1078-0432.ccr-10-2836
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Human and Mouse Dendritic Cells to VEGF Determines Interspecies Discrepancies in Tumor-Mediated Th1/Th2 Polarity Shift

Abstract: Purpose: Metastatic cancer patients exhibit systemic dysregulation of immune polarity and are biased toward Th-2 immune responses. This is due, at least in part, to effects of VEGF on antigen presenting cell (APC) function. We therefore compared immune polarity changes in mouse models of cancer with those seen in human patients.Experimental Design: We measured plasma levels of vascular growth factors and multiple cytokines via ELISA and multiplex analysis in mice with transplantable and spontaneous tumors. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Cancer vaccines have been shown to have potent antitumor effects in preclinical models of primary de novo cancers (12,15); however, these results have translated poorly to clinical trials to prevent recurrences after surgery (6). Our studies demonstrate strong vaccine efficacy when treating small (200 mm 3 ) primary tumors.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Cancer vaccines have been shown to have potent antitumor effects in preclinical models of primary de novo cancers (12,15); however, these results have translated poorly to clinical trials to prevent recurrences after surgery (6). Our studies demonstrate strong vaccine efficacy when treating small (200 mm 3 ) primary tumors.…”
Section: Discussionmentioning
confidence: 79%
“…To date, responses have been infrequent despite the generation of antigen-specific effector T lymphocytes (5,6,14). One potential explanation for the discordance between preclinical studies and postoperative clinical trials is that most evidence was derived from xenograft or transgenic mouse models with primary tumors (12,15). We propose that these studies have not considered the changes in a recurrent tumor.…”
mentioning
confidence: 99%
“…Many cancer-fighting therapies have shown strong antitumor effects in preclinical models of primary tumors but fail to translate clinically for prevention of disease recurrence after surgery (Block, Nevala 2011, Grinshtein, Bridle 2009, Schreiber, Rowley 2006, Tucker, Laguna 2012). Surgery promotes inhibitory factors that allow lingering immunosuppressive cells to repopulate minute pockets of residual disease quickly (Predina, Eruslanov 2013).…”
Section: Discussionmentioning
confidence: 99%
“…17,35,37 Several studies suggested that targeting VEGFR2 may elicit and improve the immune response directed toward the tumor and its microenvironment trough different mechanisms including direct activation of CD8 C cells and targeting of the FOXP3 high regulatory T cells. [87][88][89][90][91][92][93][94][95] These findings could explain, at least in part, the efficacy of ramucirumab, a mAb IgG1 direct to VEGFR2 and appear of interest taking also into account that GC is a disease in which VEGFR2 expression has not been reported to retain a prognostic weight. 96 Moreover, recent evidence underscored the prognostic roles of both VEGFA and VEGFC expression in GC.…”
Section: Discussionmentioning
confidence: 99%